Effectiveness and safety of Jiuwei Zhenxin granules for treating generalized anxiety disorder: A randomized controlled trial - Wang, Xue; Chen, Peiran; Shi, Shenxun; Chen, Wei; Zhang, Hongyan; Tang, Ronghua; Wu, Zhibing; Li, Yan; Wu, Jun; Zong, Li; Ji, Lianying; Feng, Ping; et al. (Frontiers in Psychiatry, 2022)
Background: Generalized anxiety disorder (GAD) is a chronic disorder characterized by excessive, pervasive, persistent worrying that is difficult to control. Jiuwei Zhenxin granules may be safer and more effective than non-benzodiazepine anti-anxiety drugs for treating GAD. This study aimed to assess the efficacy and safety of Jiuwei Zhenxin granules alone or in combination with the benzodiazepine alprazolam. Methods: A total of 710 patients were recruited from outpatient clinics and were randomly divided into two groups to receive Jiuwei Zhenxin granules (single drug group) or Jiuwei Zhenxin granules and alprazolam (combination group). The primary outcome was the response rate, which was defined as a 50% reduction from the baseline total score on the Hamilton Anxiety Scale (HAMA). Secondary outcome measures included mean changes in HAMA total score, psychological and somatic factors, Hamilton Depression Rating Scale total score and SF-36 health survey score. Results: At four weeks after treatment, the single and combination treatment groups showed significant improvement in the HAMA total score and they did not differ significantly in response rate (77.58% vs. 79.17%) or rate of adverse drug reactions (16.22% vs. 16.07%). Conclusions: Jiuwei Zhenxin granules are an effective, safe, and well-tolerated treatment against GAD. Combining them with alprazolam may not significantly improve efficacy. Trial registration: This trial was registered in the Chinese Clinical Trial Registry (registration no. CHICTR1800020095). Keywords: Generalized anxiety disorder; Hamilton Anxiety Scale; traditional Chinese medicine; Jiuwei Zhenxin granules; alprazolam